2018
DOI: 10.11648/j.ajbls.20180603.13
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antibiotic Resistance of <i>Escherichia coli</i> O157: H7 Serotype from Chicken Droppings Produced by Free - Ranged and Poultry Birds in Cross River, Nigeria

Abstract: This study investigated the prevalence of Escherichia coli O157:H7 from chicken droppings produced by free ranged and poultry birds at different locations within Cross River State, Nigeria and their susceptibility to commonly used antibiotics. A total of 360 cloacal swab samples each were randomly collected from poultry (confined) and free ranged (unconfined) chickens. Standard cultural, biochemical, and serological (latex agglutination) methods were used to isolate E. coli O157:H7. The isolates were subjected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
0
9
1
Order By: Relevance
“…The authors demonstrated that both the confined and free-range production systems harbor E. coli O157:H7 but free-range birds had the highest prevalence. They argued that the low prevalence among confined birds could be due to regular administration of antibiotics by which most poultry farmers tend to protect the birds against infection [38]. A similar result was also reported in poultry farms in Lagos and Ibadan, Nigeria [68].…”
Section: The Prevalence Of Escherichia Coli In Free-rangementioning
confidence: 56%
See 2 more Smart Citations
“…The authors demonstrated that both the confined and free-range production systems harbor E. coli O157:H7 but free-range birds had the highest prevalence. They argued that the low prevalence among confined birds could be due to regular administration of antibiotics by which most poultry farmers tend to protect the birds against infection [38]. A similar result was also reported in poultry farms in Lagos and Ibadan, Nigeria [68].…”
Section: The Prevalence Of Escherichia Coli In Free-rangementioning
confidence: 56%
“…A graphical representation of the common microbial contamination and control in free-range poultry production. Ireland 510 raw chicken products 5.1 [33] Escherichia coli Nigeria 6 study areas 11.67 [38] Ethiopia 194 cloacae swabs 13.4 [40] Cameroun 150 chickens 92.7 [41] New Caledonia 150 chickens 96.7 [41] emphasized that proper handling of poultry meat, irrespective of the production system, is important and should be taken seriously. Microbial eggshell contamination in both cage and free-range nests is comparable from well-managed facilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The isolation of E. coli was as low as 11% in free range birds of Nigeria in a study carried out by Joseph et al [23]. The variability in these findings could possibly be as a result of the differences in the type of poultry system, type of sample used and the age of the birds.…”
Section: Discussionmentioning
confidence: 94%
“…coli and E. coli O157 in food animals are available [13, 18–23]. These available Nigerian studies were conducted in the Northcentral, Southwest and Southsouth regions of the country; with reported prevalence rates ranging from 0.8–67.5%.…”
Section: Introductionmentioning
confidence: 99%